Rencang Bangun Alat Pendeteksi Aroma Urine untuk Fasilitas Umum pada Panti Jompo - Wahyudi, Hendi Nur; Mulyadi, Mulyadi (J-Eltrik, 2025)
The cleanliness of toilet facilities in nursing homes is an important factor in maintaining comfort, health, and environmental hygiene for the residents. Urine odor that is not immediately cleaned can cause discomfort and reduce the quality of sanitation in public facilities. This study aims to design and develop a urine odor detection device based on an automation system to help maintain toilet cleanliness in nursing homes. The designed system uses an ammonia gas sensor to detect urine odor, a PIR (Passive Infrared Receiver) sensor to detect user presence, LED lights for automatic lighting, and a water pump for an automatic flushing system. The research method used was an experimental method through hardware design, microcontroller programming, sensor testing, and system performance analysis. The results showed that the system worked properly through two automation features, namely automatic lighting and automatic flushing. The PIR sensor was able to automatically turn on the LED lights when detecting the presence of an object, making the toilet brighter and indicating that the toilet was being used. In addition, the ammonia gas sensor was able to detect urine odor and activate the water pump to automatically flush the toilet. The water pump stopped operating when ammonia gas was no longer detected. The designed system can help maintain toilet cleanliness, reduce unpleasant odors, and improve the efficiency of water and electrical energy usage in public facilities at nursing homes.